Caregiving process and caregiver burden: Conceptual models to guide research and practice - Brehaut Jamie; King Gillian; Rosenbaum Peter; Schwellnus Heidi; O'Donnell Maureen; Raina Parminder; Russell Dianne; Swinton Marilyn; King Susanne; Wong Micheline; Walter Stephen D; Wood Ellen (BMC, 2004)
Abstract Background Parental care for a child with a developmental disability is an enormous responsibility, one that can far exceed that of typical parental care. While most parents adapt well to the situation of caring for a child with a disability, some do not. To understand parents' adaptations to their children's disabilities, the complex nature of stress processes must be accounted for and the constructs and factors that play a role in the caregiving must be considered. Discussion Evidence suggests that there is considerable variation in how caregivers adapt to their caregiving demands. Many studies have sought to qualify the association between caregiving and health outcomes of the caregivers. Contextual factors such as SES, child factors such as child behaviour problems and severity of disability, intra-psychic factors such as mastery and self-esteem, coping strategies and social supports have all been associated with psychological and/or physical outcome or parents or primary caregivers. In reviewing these issues, the literature appears to be limited by the use of traditional analytic approaches which examine the relationship between a factor and an outcome. It is clear, however, that changes to single factors, as represented in these studies, occur very rarely even in the experimental context. The literature has also been limited by lack of reliance on specific theoretical frameworks. Summary This conceptual paper documents the state of current knowledge and explores the current theoretical frameworks that have been used to describe the caregiving process from two diverse fields, pediatrics and geriatrics. Integration of these models into one comprehensive model suitable for this population of children with disabilities and their caregivers is proposed. This model may guide future research in this area.